HUBUNGAN ASUPAN ZAT GIZI DENGAN KEJADIAN ANEMIA PADA ANAK SEKOLAH DASAR DI KABUPATEN BOLAANG MONGONDOW UTARA - Arifin, Sri Utami; Mayulu, Nelly; Rottie, Julia (JURNAL KEPERAWATAN)
Abstract: Anaemia represent the problem of sis which is often met by in clinic in all the world, beside as especial health mass of society, especially in developing countries. This Kelaianan represent penyabab of kronik debilitas having big impact to social and economic prosperity and also health of physical. Target of this research is to know relation of Asupan Iihat vitamin of Gizi with Occurence of Anaemia. This Research is executed with method of cross sectional. Sampel counted 110 taken responder at random modestly. Hereinafter data the gathered to be to be processed constructively program computer of SPSS version 19 to be analysed with test of chi-square(x2) meaning storey;level 95% (Î± 0,05). Result of Asupan Iron of showed 45 people (40,9%) which [do] not fulfill number sufficiency of gizi while fulfilling number sufficiency of gizi equal to ( 59,1%) or 65 people. Asupan Protein of showed 35 people (31,8%) which [do] not fulfill number sufficiency of gizi while fulfilling number sufficiency of gizi equal to (68,2%) or 75 people. Asupan Vitamin of C showed 24 people (21,8%) which do not fulfill number sufficiency of gizi, while fulfilling number sufficiency of gizi equal to (78,2%) or 86 people. Occurence of Anemian is showed 44 people (30%) which is anaemia, while which is anaemia do not equal to (60%) or 66 people. Conclusion There are Relation having a meaning of Asupan Iron with occurence of Anaemia with p=0,01 There are [relation/link] having a meaning of Asupan Protein with Occurence of Anaemia with p=0,01 Do not there are relation having a meaning of Asupan Vitamin of C with occurence of Anaemia with p=0,10. Keyword : intake nutrition , AnemiaAbstrak: Anemia merupakan masalah medik yang sering dijumpai di klinik di seluruh dunia, di samping sebagai massalah kesehatan utama masyarakat, terutama di negara berkembang. Kelaianan ini merupakan penyabab debilitas kronik yang mempunyai dampak besar terhadap kesejahteraan sosial dan ekonomi serta kesehatan fisik. Tujuan penelitian ini adalah untuk mengetahui hubungan Asupan Zat Gizi dengan Kejadian Anemia. Penelitian ini dilaksanakan dengan metode cross sectional. Sampel sebanyak 110 responden yang diambil secara acak sederhana. Selanjutnya data yang terkumpul diolah dengan bantuan komputer program SPSS versi 19 untuk dianalisa dengan uji chi-square (x2) pada tingkat kemaknaan 95% (Î±0,05). Hasil Asupan Besi menunjukan 45 orang (40,9%) yang tidak memenuhi angka kecukupan gizi sedangkan yang memenuhi angka kecukupan gizi sebesar (59,1%) atau 65 orang. Asupan Protein Menunjukan 35 orang (31,8%) yang tidak memenuhi angka kecukupan gizi sedangkan yang memenuhi angka kecukupan gizi sebesar (68,2%) atau 75 orang. Asupan Vitamin C menuunjukan 24 orang (21,8%) yang tidak memenuhi angka kecukupan gizi, sedangkan yang memenuhi angka kecukupan gizi sebesar (78,2%) atau 86 orang. Kejadian Anemian menunjukan 44 orang (30%) yang anemia, sedangkan yang tidak anemia sebesar (60%) atau 66 orang. Kesimpulan Terdapat Hubungan yang bermakna Asupan Besi dengan kejadian Anemia dengan p=0,01 Terdapat hubungan yang bermakna Asupan Protein dengan Kejadian Anemia dengan p=0,01 Tidak terdapat hubungan yang bermakna Asupan Vitamin C dengan kejadian Anemia dengan p=0,10.Kata Kunci: asupan zat gizi, kejadian anemia